1993
DOI: 10.1111/j.1745-4603.1993.tb00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Conformation of Tomato Pectins With Apple and Citrus Pectins

Abstract: 7'he conformation of hot break tomato pectins in water/glycerol solutions as afinction of degree esteriflcation was studied and compared with the conformation of apple and citrus pectin using reduced storage [GYR and loss [G'YR moduli and the theories of Marvin and McKinney for rod-like behavior and those of Rouse as well as Zimm for random coil conformation. In all three cases the theory of Zimm implying dominant hydrodynamic interactions p t the experimenal data best. This is consistent with current knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
3
2
Order By: Relevance
“…Past work has suggested that hot break processing inactivates pectolytic enzymes (EPG and PME), and therefore, prevents the breakdown of pectin, which is often important in product viscosity (Chou & Kokini, 1987;Goodman et al, 2002;Kokini & Chou, 1993;Xu, Shoemaker, & Luh, 1986). Our results showed that a 24 min hold time at 22°C did not allow for observable endogenous pectolytic activity on the cell-wall pectin.…”
Section: Resultscontrasting
confidence: 73%
“…Past work has suggested that hot break processing inactivates pectolytic enzymes (EPG and PME), and therefore, prevents the breakdown of pectin, which is often important in product viscosity (Chou & Kokini, 1987;Goodman et al, 2002;Kokini & Chou, 1993;Xu, Shoemaker, & Luh, 1986). Our results showed that a 24 min hold time at 22°C did not allow for observable endogenous pectolytic activity on the cell-wall pectin.…”
Section: Resultscontrasting
confidence: 73%
“…Measurements of rms radii showed that, during processing, serum pectins assumed a more compact conformation (Figures and ). It has previously been shown that the conformation of tomato paste pectins is different from other unheated pectins , . While depolymerization alone may cause conformational changes in pectins , we did not find substantial changes in serum pectin weighted average molecular weight during tomato juice concentration.…”
Section: Discussioncontrasting
confidence: 68%
“…Only the fruit and paste samples are included in Figures 7-9 to make it easier to see differences. Analysis of the pectins from the intermediate samples (2)(3)(4); not shown) generally shows trends intermediate to those depicted for paste pectins.…”
Section: Resultsmentioning
confidence: 76%
“…Texture, particularly in relationship to flow characteristics, is among the important quality attributes of processed tomato products. Several authors ( ) have reported that the most important factor in determining the viscosity and consistency of tomato paste and products derived from it is the high molar mass polymeric substances derived from cell wall polysaccharides during processing.…”
Section: Introductionmentioning
confidence: 99%